The center of the circle given by the equation (x - 3)2 plus (y + 2)2 = 9 is (3,-2).
You are describing a circle, with its center at the origin and a radius of 4 (the square root of 16)
The equation describes a circle with its centre at the origin and radius = âˆš13. Each and every point on that circle is a solution.
x2 + y2 = 49
The area of a circle is defined by the equation A = πr^2 where π = pi (3.14...) A = Area r^2 = radius squared So, the radius of a circle squared multiplied by pi equals the area.
I think this means (x+7)squared + (y-5)squared =4squared, which represents a circle centred at -7,+5
No. C = 2*pi*r is the equation representing the circumference of a circle. The area of a circle is equal to pi*(r^2).
Area of a circle equals pi (~3.14) multiplied by the radius squared. So to find the area of that circle your equation is (3.14)(3)^2 which equals approximately 27.
That's the equation of a circle with its center at the origin and a radius of 8.
It is the equation of a circle with radius of 6 and its center at the origin.
In order to take your circle and squash it horizontally to 1/2 of its original width (2),change the equation to4x2 + y2 = 16
Exactly as it's stated, that equation describes a straight line, not a circle. If you take out the phrase "times 2" from both places where it's used and replace it with "squared", then the equation describes a circle, centered at (-5, 3), with a radius of 5.
It is a quadratic equation in X.
No, It's a a quadratic equation because you have X squared.
Centre = (0,0), the origin; radius = 11
It's at the point ( -5, 3 ) The general formula of a circle is given by the equation: ( x - h )2 + ( y - k )2 = r2 Where the point ( h, k ) is the center of the circle, and r is the radius of the circle. In the equation ( x + 5 )2 + ( y - 3 )2 = 25 The first group of terms isn't subtracted. Rather than x + 5, this is actually x - -5. The center of the circle, then, is the point ( -5, 3 )
no, because xx=x squared, and x squared is not linear
Divide all terms by 2 and complete the square for x and y:- So: (x-2)^2 + (y-3)^2 = 16 Therefore centre of circle is at (2, 3) and its radius is 4
At the center, (x, y) = (-2, 5)
Pi (3.14) times the radius of a circle squared, equals the circumference of a circle.
It is the equation of a parabola.